PENERAPAN TEKNIK MEMBACA SEKILAS UNTUK MENENTUKAN GAGASAN POKOK SISWA KELAS IV SDN 015 PAGARAN TAPAH DARUSSALAM - Mariyana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the low ability of fourth-grade students at SDN 015 Pagaran Tapah Darussalam in determining the main idea of a text. The purpose of this study is to improve students’ ability to identify the main idea through the application of specific learning techniques implemented over a period of one month. The research was conducted at SDN 015 Pagaran Tapah Darussalam with the research subjects being 24 fourth-grade students. This classroom action research began in early August 2016. The instruments used in this study consisted of teacher and student activity observation sheets as well as achievement tests. Based on the results of the study, students’ skills in determining the main idea showed improvement. The preliminary data indicated a low category with a percentage of 54.2%. In the first cycle, the percentage increased to 65.1% (still in the low category), and at the second meeting of cycle I it increased again to 68.8%. In the second cycle, students’ ability increased to 81.3% (moderate category), and continued to improve in the second meeting of cycle II to 85.7% (high category).